On their own initiative: how politicians use direct democracy in the United States - Lubbock, T (2012)
The central purpose of this thesis is systematically to show why politicians use direct democracy in the US. By identifying multiple situations in which politicians make use of direct democracy, the argument that they use it for some gain is made irresistible and the reasons underlying this behaviour are brought out. Politicians are shown to use direct democracy in three arenas: before launching a candidacy for state-wide office, whilst running for state-wide office and whilst in government. Politicians are shown to do so to expand their public profile, to change campaign agendas, and at the level of the institutions of state government, to bypass another branch of government. These effects are shown using statistical tests of the occurrence of behaviour by state legislators and candidates in the first two instances. Multilevel models are used in the last two instances, to identify when state legislators and governors used direct democracy in battles over lawmaking between the branches of government. A test for the use of the legislative referral by state legislatures is particularly timely and has not been considered before. These uses together lay the groundwork for a new theory of the effects of direct democracy institutions on state government policy. The tests of policy responsiveness in later chapters reject existing theory that might provide an explanation of both why politicians use direct democracy and with what effects on state government and show on responsiveness increasing effect.